2019
DOI: 10.1042/bsr20190680
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-202 inhibits cell migration and invasion through targeting FGF2 and inactivating Wnt/β-catenin signaling in endometrial carcinoma

Abstract: Recently, many mircroRNAs (miRNAs) involved in the development and progression of cancer have been reported to regulate cell growth and metastasis, including microRNA-202 (miR-202). The purpose of the present study was to elucidate the effect of miR-202 on endometrial carcinoma (EC) cell migration and invasion. First, qRT-PCR showed that miR-202 was down-regulated in EC tissues, which was associated with poor prognosis in EC patients. Functionally, transwell assay indicated that miR-202 inhibited cell migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…For instance, the Wnt/β-catenin pathway was involved in the functions of the hsa_circ_0002577/miR-197/CTNND1 axis in EC development ( 34 ). Moreover, a study by Chen et al revealed that miR-202 inhibited cell migration and invasion through targeting FGF2 and inactivating Wnt/β-catenin signaling in EC ( 36 ). In the present study, the functions of Wnt/β-catenin signaling in EC progression regulated by miR-15a-5p were further explored.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Wnt/β-catenin pathway was involved in the functions of the hsa_circ_0002577/miR-197/CTNND1 axis in EC development ( 34 ). Moreover, a study by Chen et al revealed that miR-202 inhibited cell migration and invasion through targeting FGF2 and inactivating Wnt/β-catenin signaling in EC ( 36 ). In the present study, the functions of Wnt/β-catenin signaling in EC progression regulated by miR-15a-5p were further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that miR-202 is associated with several types of cancers such as ovarian cancer [12], lung cancer [13], and colorectal cancer [14]. miR-202 has been reported to have either a tumor-suppressive or oncogenic function (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Breast cancer blood up metastasis, poor survival outcome - [24] This discrepancy is presumed to be the result of differences in the sample processing methods, type of samples, detection methods, and characteristics of the recruited study groups.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that miR-202 is associated with several types of cancers such as ovarian cancer [ 12 ], lung cancer [ 13 ], and colorectal cancer [ 14 ]. miR-202 has been reported to have either a tumor-suppressive or oncogenic function ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review identified 105 original articles and two literature reviews reporting the expression pattern of miRNAs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%